The effects of an economic downturn on portuguese families purchase and consumption: an application to the tourism sector - Gorgueira, Joana Abreu Machado Barata (2015)
The dissertation that is now presented aims to study a phenomenon called economic downturn. In this case, the purpose is to study the effects of this problem on consumption and purchase of Portuguese families, applied to a sector that has enough impact on the economy of the country - tourism. This research, after identifying some gaps in the literature on this topic, extracted those which are the most important variables to develop a study and draw conclusions relating to purchasing behavior and consumption in a sector which has gained importance over time, using two types of methods. In the first part of the study, an extensive literature review is done. Furthermore, some data, that shows us how this problematic is currently held, is analyzed. In a second stage, a qualitative and quantitative analysis is performed. It was analyzed websites, pages, forums and blogs, in order to retrieve information from comments and analyzing what consumers think about this subject. The quantitative study involved 450 people, who were asked to give an answer to a series of questions on the topics described above. The results show that, with the economic crisis that has lived, there are a lot of changes related to the studied variables, showing the impact of an economic downturn on the consumption and purchase behavior. The way to face the future, the family’s financial situation and the sources of information are also very essential topics, as it can be seen in chapter 6 about conclusions.